Pelatihan Pemanfaatan Aplikasi Wordwall Sebagai Media Pembelajaran Interaktif pada Kelompok Kerja Guru (KKG) Kecamatan Sungai Kunjang: Pengabdian - Siska Oktaviani; Ratna Khairunnisa; Samsul Adianto; Dian Novita Amelia; Ceacilia Aureanawati Tat (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program aimed to enhance teachers' skills in utilizing the Wordwall application as an interactive learning medium in the Sungai Kunjang District, Samarinda City. The activity was conducted offline and involved 30 elementary school teachers who are members of the Teacher Working Group (KKG). The implementation began with a planning stage, which included identifying teachers' needs regarding the use of digital media in learning. The training was then delivered through the introduction of Wordwall features, demonstrations of how the application works, and hands-on practice sessions. The results of the program showed a significant improvement in teachers' ability to operate Wordwall and successfully integrate it into classroom learning activities. Students also responded positively to the use of this media, as indicated by their increased motivation and enthusiasm for learning. Furthermore, the use of Wordwall accelerated both the preparation and implementation of learning activities, thereby improving time efficiency. However, challenges remain, such as the lack of confidence among some teachers in using technology, highlighting the need for further support and guidance.